Analisis Kritis Sistem Penyelenggaraan Manajemen Pembelajaran Pendidikan Islam Di Indonesia Dalam Kemasan Scientific Learning - Irma Zaharoh (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2018)
This Articles depart from the glasses Implementation of Islamic education management that until now still experiencing significant constraints. This happens because the lack of familiarity of educational management concepts in Islamic educational institutions. The issues discussed in this journal article include: What is the Basic Concept of Management of Learning? How is the Islamic Education Institution in Indonesia? And how the System of Implementation of Islamic Education Learning Management in Indonesia (in Packaging Scientific Learning). The basic concept of learning management at least there are three basic elements that must be managed in the context of implementation of education management in Islamic educational institutions, namely: student management, management personnel, and curriculum management and teaching programs. As stated in Law No. 20 of 2003 on National Education System, Educational Institutes are grouped into three groups, namely Formal Islamic Education, Non-Formal Islamic Education, and In-Formal Islamic Education. Implementation of Education System in Indonesia has been arranged clearly in the Act SISDIKNAS then translated into Government Peratuaran and then operated in Meneteri Peratuaran.